2022
DOI: 10.3389/fbioe.2022.1003966
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of regional human meniscus progenitor cells

Abstract: Stimulating meniscus regeneration using meniscal progenitor cells has been suggested as a promising new strategy. However, there is a lack of studies which decisively identify and characterize progenitor cell populations in human meniscus tissues. In this study, donor-matched progenitor cells were isolated via selective fibronectin adhesion from the avascular and vascular regions of the meniscus and chondroprogenitors from articular cartilage (n = 5). The mixed populations of cells from these regions were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Recent studies investigated the phenotype of meniscal cells using flow cytometry and single cell Frontiers in Bioengineering and Biotechnology frontiersin.org sequencing. They found regional differences with high amounts of CD90-positive cells and up to seven independent cell clusters (Sun et al, 2020;Wang et al, 2022). The low amount of CD146-positive cells in this study might indicate towards a special phenotype found in degenerated menisci: degenerated meniscus progenitor cells (DegP) (Sun et al, 2020).…”
Section: Discussionmentioning
confidence: 49%
“…Recent studies investigated the phenotype of meniscal cells using flow cytometry and single cell Frontiers in Bioengineering and Biotechnology frontiersin.org sequencing. They found regional differences with high amounts of CD90-positive cells and up to seven independent cell clusters (Sun et al, 2020;Wang et al, 2022). The low amount of CD146-positive cells in this study might indicate towards a special phenotype found in degenerated menisci: degenerated meniscus progenitor cells (DegP) (Sun et al, 2020).…”
Section: Discussionmentioning
confidence: 49%
“…Cell growth assessment was performed utilizing the Cell-IQ real-time cell monitoring platform (Chip-Man Technologies, Tampere, Finland) according to methodology adapted from the method described by Wang et al [ 72 ]. Then, 10 4 HaCaT keratinocytes were seeded into individual wells of a 24-well cell culture plate containing S10 medium (DMEM supplemented with 1% penicillin (100 U mL −1 )–streptomycin (100 μg mL −1 ) (P/S) and 10% fetal bovine serum (FBS, Sigma, St. Louis, MO, USA)).…”
Section: Methodsmentioning
confidence: 99%
“…Scaffolds are essential in structural-oriented approaches to engineering meniscus tissues because they provide three-dimensional templates for cell growth and tissue formation ( Bilgen et al, 2018 ; Wang J et al, 2022 ). Structurally, the meniscus is featured by the unique gross crescent shape with hierarchical and intertwined fibrous ECM, which enables its good capability to resist complex loads in the knee joint ( Li et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%